JUAL BELI BERDASARKAN KITAB UNDANG-UNDANG HUKUM PERDATA DAN HUKUM ISLAM (AL QUR’AN-HADIST) SECARA TIDAK TUNAI - Umardani, Mohamad Kharis (Journal of Islamic Law Studies, 2021)
This study aims to analyze the sale and purchase regulation contained in the Indonesian Civil Code (KUHPerdata) and Islamic law from Al Quran and Hadith, also the solution of the problem of sale and purchase by credit either in Indonesian Civil Code (KUHPerdata) and Islamic law. These studies are descriptive analytical method using normative juridical approach to statute approach. Indonesian Civil Code regulates the Sale and Purchase on article 1457, a sale and purchase is an agreement, by which one party is bound to deliver a certain matter, for which the other party shall pay a stipulated price. Islamic law also had a regulation about sale and purchase, definition of Fiqh scholars about sale and purchase is the process of exchange of property, or a benefits/services are allowed to exchanged for similar things for an unlimited period, in ways that justified. Definition sale and purchase above given by KUHPerdata and Islamic law there is a similiarity that is a sale and purchase is an konsensuil agreement whereby the seller deliver their property rights, while a buyer giving the money. In fact when sale and purchase in credit, not in accordance with rule KUHPerdata or Islamic law i.e. involving third parties could be termed "Triangle Sale and Purchase".